Effect of dietary supplementation of Shatavari on productive performance and fertility of crossbred cows: Shatavari (Asparagus racemosus) of Performance on Crossbred Cows - Muwal, Hitesh; Rai, Dinesh Chandra; Bhateshwar, Vinod; Arvind; Duary, Raj Kumar; Lal, Dwarki (Indian Journal of Dairy Science, 2023)
The aim of the present study was to demonstrate the effect of oral administration with Shatavari (Asparagus racemosus) on milk yield, raw milk constituent indices and fertility of crossbred cows during summer season. Twenty healthy lactating crossbred cows with a close date of calving were randomly divided into two equal groups for control group (CG; n = 10) and supplemented group: Shatavari root powder 50 gm/cow/d (SG; n = 12) from 7 days post partum (dpp) until 90 dpp. Statistically analyzed data revealed that fortnightly milk yield significantly (P0.005), but only fortnightly percent of milk solid not-fat from 45 to 90 dpp in SG cows (9.254 to 9.446%) than over to CG cows (8.877 to 8.999%) and percent of milk total solids from 60 to 90 dpp cows in SG (13.078 to 13.727%) than that cows in CG (12.617 to 12.648%) were significantly (P